Regulatory arbitrage under Basel proposals - Chroustovský, Jiří (2012)
Bachelor thesis deals with the phenomenon of regulatory arbitrage. The work seeks to identify opportunities for regulatory arbitrage under Basel I and Basel II accords. The aim of the thesis is to determine whether banks engaged in regulatory arbitrage, and how it affected the financial system. In examining regulatory arbitrage, it was found that the Basel I and Basel II provided a potential for regulatory arbitrage, and banks did not hesitate to engage in it. The thesis identifies that the main problem of banking regulation is the change in incentives of players in the financial markets leading to regulatory arbitrage, and consequently to a greater concentration of risk in financial markets. The work suggests a creation of the fourth pillar of the Basel accords, which would provide rules for bank resolution mechanisms. Thus, it tries to alleviate the problem of moral hazard currently present in the banking system.